2007
DOI: 10.4028/www.scientific.net/kem.353-358.2293
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Crack Growth Rate and Magnetic Memory Signal of X45 Steel

Abstract: Crack growth rate, as an important parameter, is widely applied in crack growth evaluation and fatigue life prediction. The objective of this paper is to study crack growth rate with the metal magnetic memory (MMM) technology which is a non-destructive testing method newly developed. The correlation between crack growth rate da / dN and magnetic memory signal Hp(y) is investigated through three-point bending fatigue testing. Samples of steel X45, with different heat treatments, quenching and thermal refining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In graphical observation, the rate of crack growth, da/dN, was increased simultaneously with the increasing of magnetic flux leakage towards the surface of the metal with the R-Squared values in the range of 0.7387 to 0.8863 respectively. It can also be clearly seen that the patterns of the curves (for all specimens) showed an identical trend, with a sigmoid shape (Xing et al 2007).…”
Section: The Formation Of Magnetic Signalsmentioning
confidence: 60%
See 1 more Smart Citation
“…In graphical observation, the rate of crack growth, da/dN, was increased simultaneously with the increasing of magnetic flux leakage towards the surface of the metal with the R-Squared values in the range of 0.7387 to 0.8863 respectively. It can also be clearly seen that the patterns of the curves (for all specimens) showed an identical trend, with a sigmoid shape (Xing et al 2007).…”
Section: The Formation Of Magnetic Signalsmentioning
confidence: 60%
“…Furthermore, Dong et al (2010a) discussed MMM signal characteristics in the tension-tension fatigue testing of notched plate specimens; and reported that the MMM signals are intensively affected by many factors, such as different load types, machining processes, heat treatment conditions, and extra magnetic fields, which prevent MMM testing from being widely used in practical projects. This was further enhanced by Xing et al (2007) in studying the correlation between the crack growth rate, da/dN, and magnetic memory signal Hp(y) through a three-point bending fatigue testing. Wang et al (2012) also reviewed the fundamentals of MMM technology as an effective method in assessing the early damage and defects by detecting the surface of metal depth of up to several millimeters with a maximum measuring velocity of up to several meters per second.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed from the graphs in Figure 4, that the abnormal magnetic peak (drastic change) occurred in the middle of the scanning distances (45 mm to 55 mm), which appears under the notch areas of the specimen. Indeed, this mechanism is either plastically induced by crack closure or crack rate retardation associated with the plastic zone ahead of a crack tip, in which the tensile overload cycle leads to the crack tip sharpening and the crack rate increasing (Wu et al, 2010;Xing et al, 2007). Also, the signals of Hp(y) and dHp/dx in Figure 4(a) show the standard magnetic signals with weak changes in specific areas on the surface of a specimen.…”
Section: Probabilistic Approachmentioning
confidence: 99%
“…As displayed, the pattern of this plot is similar to that of the second region in Figure 2 Hypothetically, dH(y)/dx and ∆K are similar in the sense that they both indicate the state of stress during fatigue crack growth. Xing et al [11] and Ahmad et al [19] investigate relationship between ∆K and H(y) and it was stated that H(y) variation reflects the change of stress intensity factor ∆K during the whole crack growth process and linear relation was represented between ΔK and H(y) graph. Figure 6 illustrates the investigation conducted on the relationship between dH(y)/dx and ∆K.…”
Section: Relationship Between Magnetic Flux Gradient Signals Dh/dx Amentioning
confidence: 99%
“…A substantial number of studies have been performed in efforts to link the MMM signals to fatigue crack growth parameters. Xing et al [11] investigated the association between the crack growth rate da/dN and the MMM regular component signal H(y). It was observed that the H(y) increased in tandem with the rise of da/dN while the correlation curve between H(y) and da/dN exhibited a sigmoidal figure.…”
Section: Introductionmentioning
confidence: 99%